Assessment in Physics and in Chemistry: what kind of learning is favoured in secondary school teaching? - Claudia Alejandra Mazzitelli; Ana María Guirad; Adela del Carmen Olivera (Investigações em Ensino de Ciências, 2013)
The teaching and learning process of Natural Science, nowadays, presents some difficulties which become evident, among others, in the students’ low academic achievement. With the aim of deepening our knowledge about this problem in order to promote actions which contribute to the improvement of the quality of the educational system, we carried out an experience during which we studied the processes involved in the teaching and learning of Physics and Chemistry. Secondary school students and teachers of Physics and Chemistry took part in the experience. We believe that assessment is a key factor of the teaching and learning process and of the school curriculum development. For this reason, we analyzed the evaluations that teachers carry out in class and their interrelationship with the teaching-learning process. The strategies implemented by the teachers, as well as the evaluation process, have allowed us to infer the background which supports their conception of what learning science means. The results obtained suggest that students have better achievement when they are asked to memorize, and this could be related to the students’ low performance in activities which demand more complex cognitive abilities. Favouring a learning process based only on memory may lead to erroneous conceptions about the building up of scientific knowledge and, besides, may not contribute to the development of meaningful and autonomous learning.